Look who's talking - Alley, Kirstie; Travolta, John, 1954-; Dukakis, Olympia; Segal, George; Vigoda, Abe, 1921-2016; Willis, Bruce, 1955-; Heckerling, Amy.; Tri-Star Pictures; Columbia TriStar Home Video (Firm) (Culver City, CA : Columbia TriStar Home Video, 1997)
Mollie (Kirstie Alley) is a single working mom who's out to find the perfect father for her child. Her baby, Mikey, prefers James (John Travolta), a cab driver turned babysitter who Mollie won't even consider. It's going to take all the tricks a baby can think of to bring them together before it's too late.
Title from container.
Videodisc of the 1989 motion picture.
Closed-captioned.
Music score by David Kitay.
John Travolta, Kirstie Alley, Olympia Dukakis, George Segal, Abe Vigoda, and Bruce Willis as the voice of "Mikey."
Rated PG-13.
Keywords: Infants -- Drama; Families -- Drama; Feature films; Comedy films; Features; Comedies